The genetic technologies questionnaire: lay judgments about genetic technologies align with ethical theory, are coherent, and predict behaviour - Küchenhoff, Svenja; Doerflinger, Johannes; Heinzelmann, Nora (BMC medical ethics, 2022)
Policy regulations of ethically controversial genetic technologies should, on the one hand, be based on ethical principles. On the other hand, they should be socially acceptable to ensure implementation. In addition, they should align with ethical theory. Yet to date we lack a reliable and valid scale to measure the relevant ethical judgements in laypeople. We target this lacuna.